Radon Measurements in Bottled Waters in Greece - Stamoulis, K. C.; Ioannides, K. G.; Patiris, D. C. (HNPS Advances in Nuclear Physics, 2020)
Underground waters pass through various types of rocks, which may contain radium and uranium isotopes in such concentrations and chemical forms that could be diluted in the water body. Thus it is possible to contain significant quantities of these radioisotopes such as radium (226Ra), which decays producing a series of alpha and beta emitters that remain in the water. Among them, radon (222Rn) and isotopes of polonium (214Po and 218Po) contribute to significant doses. In this work, we measured radium/radon concentration levels in bottled waters commercially available in Greece. Samples were concentrated by a factor of 20-100, in order to obtain more accurate results, because in the majority of the samples the concentrations measured initially were very low. To measure the radioactivity concentrations, 10 mL of concentrated sample were added to 10 mL of scintillation cocktail in a 20 mL plastic vial and then were counted with a liquid scintillation analyzer. The results show that radium/radon concentrations of the bottled waters range from 7-70 mBq/L.